PENGEMBANGAN MEDIA PEMBELAJARAN BAHASA DAN SASTRA INDONESIA MENGGUNAKAN APLIKASI CANVA TINGKAT SD/MI - Adam Mudinillah; Fera Hifayatil Fitri (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
Indonesian is a compulsory subject, whether it is implemented in elementary, junior high, and high school, as well as in universities, always at the education level. Language is a collection of meaningful words, or meanings derived from words. The use of learning media will make it easier for students to understand and learn. The method or steps used in this research is a qualitative descriptive method, with the following techniques: Analysis of results. The analytical aspects are fluency, flexibility, Originality and exposition. The research was carried out in two cycles. Learning to present materials for writing and designing curriculum vitae and job application letters using the Canva Cycle 1 application is carried out in one meeting.Keywords: canva, learning media, bahasa.